2016
DOI: 10.1016/j.ejim.2016.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based clinical practice: Overview of threats to the validity of evidence and how to minimise them

Abstract: Abstract.Using the best quality of clinical research evidence is essential for choosing the right treatment for patients. How to identify the best research evidence is, however, difficult. In this narrative review we summarise these threats and describe how to minimise them. Pertinent literature was considered through literature searches combined with personal files. Treatments should generally not be chosen based only on evidence from observational studies or single randomised clinical trials. Systematic revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 94 publications
0
107
1
Order By: Relevance
“…We used central randomisation stratifying for important predictive factors,51 52 53 54 used blinded outcome assessors,51 52 53 54 assessed several register based outcomes that are likely less influenced by knowledge about intervention group affiliation than other outcomes, included stratification factors in our main analyses,55 56 conducted our main analyses on the data where missingness was controlled by multiple imputation,57 58 conducted our analyses blinded for intervention group,59 and drew our conclusions without knowledge of intervention group 59. Moreover, although we based our sample size calculation on a power of 80%, by inflating our sample by 30% and analysing all participants using multiple imputations, we actually had a power of 91% to detect the a priori defined least significant difference regarding the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used central randomisation stratifying for important predictive factors,51 52 53 54 used blinded outcome assessors,51 52 53 54 assessed several register based outcomes that are likely less influenced by knowledge about intervention group affiliation than other outcomes, included stratification factors in our main analyses,55 56 conducted our main analyses on the data where missingness was controlled by multiple imputation,57 58 conducted our analyses blinded for intervention group,59 and drew our conclusions without knowledge of intervention group 59. Moreover, although we based our sample size calculation on a power of 80%, by inflating our sample by 30% and analysing all participants using multiple imputations, we actually had a power of 91% to detect the a priori defined least significant difference regarding the primary outcome.…”
Section: Discussionmentioning
confidence: 99%
“…From top to bottom, graphs show development of negative symptoms (mean score on the scale for assessment of negative symptoms (sans)), psychotic symptoms (mean score on the scale for assessment for positive symptoms (saPs)), functional level (mean score on the personal and social performance scale (PsP)), and cognitive functioning (mean total score on the brief assessment of cognition in schizophrenia (baCs)) from baseline to follow-up strengths and limitations of study Strengths We used central randomisation stratifying for important predictive factors, 51-54 used blinded outcome assessors, [51][52][53][54] assessed several register based outcomes that are likely less influenced by knowledge about intervention group affiliation than other outcomes, included stratification factors in our main analyses, 55 56 conducted our main analyses on the data where missingness was controlled by multiple imputation, 57 58 conducted our analyses blinded for intervention group, 59 and drew our conclusions without knowledge of intervention group. 59 Moreover, although we based our sample size calculation on a power of 80%, by inflating our sample by 30% and analysing all participants using multiple imputations, we actually had a power of 91% to detect the a priori defined least significant difference regarding the primary outcome.…”
Section: Fig 2 |mentioning
confidence: 99%
“…This point of view seems to unduly emphasise the difference between the consequences of an interim-analysis in a single trial and the consequences of a sequential meta-analysis of several trials. First, the systematic review is placed at the top of the generally recognised hierarchy of evidence, meaning that the systematic review is considered the most likely reliable source of evidence, implicating whether an intervention should be implemented in clinical practice or further trials should be launched [52, 53]. Interventions are often recommended in clinical guidelines and implemented in clinical practice when a meta-analysis shows statistical significance on the traditional naïve level ( P  < 0.05) [16, 18, 6769].…”
Section: Discussionmentioning
confidence: 99%
“…Another potential limitation when using composite outcomes, such as serious adverse events, is that each component of a composite outcome will not have similar degrees of severity, so event severity differences between the compared groups might not be shown in the analysis of such outcomes 18. Finally, we found no evidence of a difference when assessing all-cause mortality, cardiovascular mortality and myocardial infarction, and Trial Sequential Analyses showed that we do not have enough information to confirm or reject our anticipated intervention effects.…”
Section: Limitationsmentioning
confidence: 99%